Anti-inflammatory Activity of Kappaphycus Alvarezii Using Protein Denaturation Inhibition Method - Windy Zafa Amalia; Sulastrianah; Arimaswati (MEDULA: Jurnal Ilmiah Fakultas Kedokteran Universitas Halu Oleo, 2024)
ABSTRACT Background: Inflammation is the body's reaction to injury or tissue damage. As an NSAID, diclofenac sodium is frequently used. But since this medication has adverse effects, a substitute is required. Flavonoids found in K. alvarezii may have therapeutic uses and anti-inflammatory potential. Purpose: The goal of this research was to investigate the anti-inflammatory effect of K. alvarezii utilizing the protein denaturation inhibition method. Method: The IC50 was utilized to test anti-inflammatory effect through protein denaturation inhibition. Diclofenac sodium served as a positive control. The data were then analyzed with an independent t-test. Result: The anti-inflammatory activity test produced an IC50 of 197.94 ppm for extract K. alvarezii and 35.7 ppm for diclofenac sodium. The statistical test found a significant difference between seaweed ethanol extract K. alvarezii and sodium diclofenac (p = 0.000). Keywords: anti-inflammatory; Kappaphycus alvarezii; protein denaturation inhibition.